Search for vector mediator of dark matter production in invisible decay mode; Physical Review D; Vol. 97, iss. 7 - Banerjee D.; Crivelli P. Paolo; Burtsev V. E. Vitaly Evgenjevich; Chumakov A. G. Aleksandr Grigorjevich; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Trifonov A. Yu. Andrey Yurievich; Vasilishin B. I. Bogdan Ivanovich (2018, 2018)
Title screen